Augmented reality and ethical reasoning: A mini review of pedagogical frameworks and future directions in secondary education - Shegaram, Punggothai Chandra; Balakrishnan, Balamuralithara; Naidu, Noor Banu Mahadir (Journal of Islamic, Social, Economics and Development, 2026)
This mini-review brings together recent research (from 2020 to 2025) on how Augmented Reality (AR) can help students in secondary school learn about morals and ethics better, when guided by three key frameworks: Universal Design for Learning (UDL), the Cognitive Theory of Multimedia Learning (CTML), and Rest’s Four Component Model (FCM). AR is no longer just seen as a way to make learning more fun; it can now place students in realistic situations where they have to think about right and wrong, understand different viewpoints, and reflect thoughtfully through interactive and immersive experiences. To find this information, a detailed search was done across several academic databases like Scopus, Web of Science, ScienceDirect, SpringerLink, and Google Scholar. The search used specific key terms like AR, immersive technology, moral or ethical education, secondary education, and the three frameworks mentioned. Using a process based on PRISMA, only peer-reviewed English articles published between January 2020 and December 2025 were included, and other types of studies or non-peer-reviewed materials were left out. The findings show that AR works best when its design clearly includes (a) UDL to support different types of learners and make things more accessible, (b) CTML to help students process information without getting overwhelmed, and (c) FCM to move from understanding moral issues to making decisions, being motivated to act morally, and actually doing something about it. However, the research also shows some problems: many AR projects focus on quick engagement and short discussions without showing that students apply these lessons in real life; there’s not always consistency in using CTML, which can lead to confusion or overload; and AR isn’t often used in a way that covers all parts of the FCM, especially when it comes to taking action. Overall, the review finds that AR can help students in secondary school develop better moral reasoning, but its success depends on using these frameworks in a thoughtful way, checking its long-term effects, and using better ways to measure how students’ morals and behaviors change.